How communication scholars think and act : a lifespan perspective - Mirivel, Julien C. 1978- (Lifespan communication (Peter Lang), 2017)
Every great scholar begins as a student. But what does it take to get there? And what is the journey like? This book explores the lifespan development of some of the best-known communication scholars in the United States. Grounded in 30 in-depth interviews, personal stories, and communication theory, the book reveals the nature of human development, the curvature of disciplinary thinking, and the values that drive communication professionals. With powerful examples from great thinkers and teachers such as Robert Craig, Valerie Manusov, and Gerry Philipsen, the book shows that communicating well is a slow, gradual awakening toward others. 'How Communication Scholars Think and Act' is designed to inspire students and faculty alike to persevere in the face of setbacks, to learn about communication more deeply, and to improve human relationships across contexts. This is an ideal text for courses in communication theory, interpersonal communication, and introductory courses to the field. It is a must-read for anyone who wants to become a communication professional.